Learning English Listening Using Learning English Listening Using Media Busuu Application: Learning English Listening Using Media Busuu Application - Nana Priajana; Nafa, Lina Nafasatul Ilmi; Tedi Rohadi (STIT Buntet Pesantren Cirebon, 2023)
This research discusses the use of Busuu app as a learning platform for English listening skills in junior high schools in Cirebon. The research focuses on the importance of media use in language teaching and the role of media in creating a conducive learning environment. It also explores the theoretical basis of language skills, learning media and the use of Busuu app to teach English listening skills. This researchers used qualitative methods, precisely descriptive qualitative. The purpose of this study to obtain students' views on the use of the Busuu application as a learning platform, to determine student achievement in learning through the Busuu application as a listening learning media and to find out the advantages and disadvantages of the Busuu application. The data source of this research is the documentation of the learning process. The text is taken from the results of interviews with students and teachers of class VIII. The instrument of this research is the researcher himself. In addition, other instruments used by researchers are documentation, interview transcripts, audio recordings, and documents. The results showed that, (1) The use of media in learning is one of the efforts to provide quality in supporting the learning process and can encourage students to take part in learning activities in a fun way. (2) The Busuu application is an application specifically designed to support web-based English language learning and is also available as a mobile application and is one of the main alternatives that is very easy to access. (3) The Busuu application has advantages and disadvantages of the Busuu Application. So, it can be concluded that the Busuu application directly has a positive influence on SMP N 1Lemahabang students.